(untitled) (CIPEEX, 2025)
Endocrowns are crowns anchored in the pulp chamber in the cervical region of the root and do not require intraradicular preparation. An easy-to-perform technique, it demands less clinical time compared to traditional single crowns with posts and cores. The objective of this work was to evaluate the influence of the presence of a ferrule and preparation extension on the biomechanical behavior of endodontically treated premolars. The study factors were: 1. presence of ferrule (with or without) and 2. extension of the preparation for the endocrown (2, 3, and 4mm). The response variables were: Maximum principal stress (σmax) and von Mises stress for all structures involved. Models with a ferrule and 2 mm presented the highest values. When observing the compression stresses, it was found that the highest stress values were found in models with a ferrule of 2 and 4 mm. When evaluating the compression stress on the crown, a smaller difference between the groups was found, with the highest values occurring in models without a ferrule. For tensile stresses, the different preparation heights for the endocrown did not affect the results on the crown and root. For compression stresses, the different preparation heights for the endocrown did not affect the results on the crown and root, and for both teeth with and without a ferrule, the highest stress values were found in the 4 mm preparations. Within the limitations of an in silico study, it can be concluded that for tensile stresses, the different preparation heights for the endocrown do not affect the stress concentrations on the crown and root.